The Impact of Termite Activity on Soil Fertility: A Case Study in Pine Stands in the Alas Bromo Education Forest Area - Sri Rezeki Febriani; Dwi Priyo Ariyanto; Ongko Cahyono; Rahayu Rahayu; Didi Tarmadi (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Termites function as soil engineers and play a crucial role in the decomposition of organic matter. This study was conducted in the Alas Bromo Educational Forest under pine stands of various age classes. The objective of the research was to investigate the influence of termite activity on soil fertility, as indicated by the levels of soil organic matter (SOM), soil organic carbon (SOC), and soil pH. The method employed involved baiting pinewood stakes placed in polyvinyl chloride pipes (PVC) to assess termite activity, which was evaluated based on the level of damage to the stakes and classified into damage classes. The stakes used were made of pine wood, similar to the species of the overlying stands. This study identified four termite genera in the Alas Bromo area: Macrotermes, Microtermes, Odontotermes, and Schedorhinotermes. The findings revealed significant differences in SOM and SOC across the stake damage classes within each stand. In general, the highest values were observed in soils with the highest levels of termite activity, as reflected in damage class 4. However, soil pH values did not show significant differences across the varying levels of termite activity. These findings highlight that termites, as soil engineers, play a vital role in enhancing soil fertility and hold promising potential for application in the pursuit of sustainable agriculture.